2017
DOI: 10.1371/journal.pone.0169321
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Vocalic Proto-System in the Baboon (Papio papio) Suggests Pre-Hominin Speech Precursors

Abstract: Language is a distinguishing characteristic of our species, and the course of its evolution is one of the hardest problems in science. It has long been generally considered that human speech requires a low larynx, and that the high larynx of nonhuman primates should preclude their producing the vowel systems universally found in human language. Examining the vocalizations through acoustic analyses, tongue anatomy, and modeling of acoustic potential, we found that baboons (Papio papio) produce sounds sharing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 36 publications
3
96
0
Order By: Relevance
“…In the first study to document ear advantages for acoustic stimuli in a nonhuman primate species, Pohl [137] found highly significant and reproducible ear advantages in four baboons (Papio cynocephalus) for the monaural discrimination of pure tones, three-tone musical chords, synthetically-constructed consonant-vowels (CVs) and vowels in each of the animals with marked individual differences in the direction of ear asymmetry. The ear advantages found in these baboons under monaural conditions resembled those obtained with dichotic presentation in human subjects [138] and thus suggest-especially when considered together with the recent findings [135] on the vowel-like quality of baboon vocalizations mentioned above-that the baboon may provide a valuable nonhuman primate model of functional asymmetry in the central auditory system. In a subsequent study on ear advantages for temporal resolution in the same four baboons, Pohl [139] hypothesized that the temporal resolution which underlies the individual animal's ear advantage for speech perception, would predict an ear advantage in a temporal resolution task to correlate precisely with an ear advantage for the discrimination of CVs that differ in their temporal features.…”
Section: Read-do Correspondencesupporting
confidence: 75%
See 1 more Smart Citation
“…In the first study to document ear advantages for acoustic stimuli in a nonhuman primate species, Pohl [137] found highly significant and reproducible ear advantages in four baboons (Papio cynocephalus) for the monaural discrimination of pure tones, three-tone musical chords, synthetically-constructed consonant-vowels (CVs) and vowels in each of the animals with marked individual differences in the direction of ear asymmetry. The ear advantages found in these baboons under monaural conditions resembled those obtained with dichotic presentation in human subjects [138] and thus suggest-especially when considered together with the recent findings [135] on the vowel-like quality of baboon vocalizations mentioned above-that the baboon may provide a valuable nonhuman primate model of functional asymmetry in the central auditory system. In a subsequent study on ear advantages for temporal resolution in the same four baboons, Pohl [139] hypothesized that the temporal resolution which underlies the individual animal's ear advantage for speech perception, would predict an ear advantage in a temporal resolution task to correlate precisely with an ear advantage for the discrimination of CVs that differ in their temporal features.…”
Section: Read-do Correspondencesupporting
confidence: 75%
“…This topic, which has always been puzzling to evolutionary biologists, has recently been investigated by Masataka [132] [133]. In a similar vein, theorizing with a view towards 'a more comprehensive understanding of language,' Greer In a recent descriptive study in baboons, Boë and colleagues [135] Seyfarth and Cheney [136] recently found that despite their limited vocal repertoire, Papio ursinus females were skilled at modifying call production in different social contexts and for different audiences (e.g., vocalizing towards mothers with young infants but not towards females without infants). We may assume that the socially selective production of calls in these female baboons presupposes a complementary selective listening behavior in their female counterparts.…”
Section: Read-do Correspondencementioning
confidence: 99%
“…This conclusion seems to us to be strongly favored by all available data, particularly our new study and other recent work ( 32 ), and Lieberman’s technical comment provides no new grounds for disputing it.…”
Section: Resultssupporting
confidence: 46%
“…[65][66][67][68][69] The most convincing possibility, suggested by Philip Lieberman and colleagues, was that the lowering of the human larynx and resulting reconfiguration of the human vocal tract makes a range of sounds possible (particularly the "point vowels" /i/, /a/, and /u/ of "beet," "bought," and "boot," respectively) that would otherwise be impossible to produce with a nonhuman primate vocal tract (which is not the same as claiming that these anatomical changes are necessary for complex vocal learning). But even this more modest hypothesis has been convincingly challenged based on computer models and data from nonhuman primate vocalizations, 70,71 along with X-ray observations showing that all mammals studied spontaneously lower the larynx during vocalization. 72 My colleagues and I recently reexamined this issue by capturing X-ray videos of macaques vocalizing and producing other vocal tract movements (facial gestures, such as yawns and lip smacks, along with chewing and swallowing).…”
Section: Changes In Vocal Anatomy Are Neither Necessary Nor Sufficienmentioning
confidence: 99%